Distinct modes of East Asian Winter Monsoon documented by a southern Red Sea coral record. Issue 3 (5th March 2014) - Ionita, Monica; Felis, Thomas; Lohmann, Gerrit; Rimbu, Norel; Pätzold, Jürgen
Abstract The large‐scale boreal winter climatic patterns associated with interannual variability in a coral oxygen isotope (δ18O) record from the southern Red Sea covering most of the last century are investigated. From the early 1930s to the early 1960s, the winter coral δ18O record, reflecting temperature and salinity variations in southern Red Sea surface waters, is associated with global (or large scale) sea surface temperature (SST) and 850 mb geopotential height (Z850) anomalies which project on the corresponding patterns associated with the El Niño‐Southern Oscillation (ENSO). In contrast, since the early 1960s the winter coral δ18O record is related to a Z850 pattern that reflects the ENSO‐independent part of the East Asian Winter Monsoon (EAWM), which includes the Siberian High, the East Asian through, and the East Asian upper‐tropospheric Jet. Our results indicate a weakening of the ENSO control on interannual temperature/salinity variations in southern Red Sea surface waters in the early 1960s, due to the warming of the Indian Ocean, and suggest that information about the nonstationarity in the relationship between ENSO and two distinct modes of EAWM can be documented in southern Red Sea coral δ18O records.